Pengaruh Budaya & Bargaining Power Terhadap Partisipasi Kerja dan Sekolah Anak di Jawa Timur - Amir, Faishol; Ashar, Khusnul; Pratomo, Devanto Shasta (Jurnal Ekonomi Kuantitatif Terapan; 2019: Vol. 12, No.1, Februari 2019 (pp. 1-107)DO - 10.24843/JEKT.2019.v12.i01.p01, 2018)
This paper examines the influence of cultural and bargaining Power on child labor and school participation in East Java. The prevalence of children aged 10-17 years who work in East Java is around 4.74%. About 28.03% of children who work are still in school. Whereas school dropouts reach 11.28%. Referring to the theory of collective model and using the method of multinomial logit regression analysis on the Intercensal Population Survey (SUPAS) data in 2015, this paper concludes that culture proxied through tlatah had a significant effect. Children who come from Arek tlatah are most likely to work. Children from the Pandalungan tlatah are the least likely to go to school. While children from Madura Pulau tlatah are most likely to go to school while working.. Interestingly, if maternal education is equal or even higher than that of fathers, children's participation in work increases and conversely the participation of school children actually decreases.